2012
DOI: 10.1017/jfm.2012.163
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional effects in hovering flapping flight

Abstract: This paper aims at understanding the influence of three-dimensional effects in hovering flapping flight. Numerical simulations at a Reynolds number of 1000 are performed to compare two types of flapping kinematics whose plunging phase is characterized by either a rectilinear translation or a revolving motion. In this way, we are able to isolate the three-dimensional effects induced by the free end condition from that induced by the spanwise incident velocity gradient (and the associated implicit Coriolis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 27 publications
7
39
0
Order By: Relevance
“…The resulting spatio-temporal evolution of all three vorticity components is provided in figure 10. In accordance with the reports of Jardin et al (2012), neither streamwise (tip) nor plate-normal vorticity are significant in the midplane region, which supports the previous assumption of two-dimensional LEV formation.…”
Section: Direct Force Measurementssupporting
confidence: 91%
See 3 more Smart Citations
“…The resulting spatio-temporal evolution of all three vorticity components is provided in figure 10. In accordance with the reports of Jardin et al (2012), neither streamwise (tip) nor plate-normal vorticity are significant in the midplane region, which supports the previous assumption of two-dimensional LEV formation.…”
Section: Direct Force Measurementssupporting
confidence: 91%
“…In the two-dimensional analysis of the plate's near-midplane region, as defined by Jardin et al (2012), it has been shown that the effective velocity U eff of the feeding shear layer is the appropriate characteristic velocity rather than the more commonly used plungeḣ or free stream U ∞ velocities. It is therefore proposed that the non-dimensionalization for various plate kinematics should be based on the effective feeding shear-layer velocity since it dictates vortex growth and thus overall force histories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results show that there existed a strong spanwise flow on the flapping wing in hovering flight. As suggested by previous studies [5,7], the spanwise flow that may drain energy from the LEV, and thus limited its downstream chordwise development and prevented the wings from stalling. However, the increase of non-dimensional spanwise velocity, u * span , from the wing root to the middle wing-span also suggests that the spanwise flow may stretch the LEV along the wing and hence helped to prolong the attachment of LEV [8].…”
Section: Flight Simulationsmentioning
confidence: 76%